The Transthyretin Inflammatory State Conundrum - H. Bernstein, Larry (Current Nutrition & Food Science, 2012)
Background: Transthyretin has been widely used as a biomarker for identifying protein-energy malnutrition (PEM) and for monitoring the improvement of nutritional status after implementing a nutritional intervention by enteral feeding or by parenteral infusion. This has occurred because transthyretin (TTR) has a rapid removal from the circulation and it is readily measured. Nevertheless, concerns have been raised about the use of TTR in the ICU setting, which prompts a review of the actual benefit of using this testing in a number of settings. TTR is easily followed in the underweight and the high risk populations in an ambulatory setting, which has a significant background risk of chronic diseases. It is sensitive to the systemic inflammatory response syndrome (SIRS), and needs to be understood in the context of acute illness to be used effectively. There are a number of physiologic changes associated with SIRS and the injury/repair process that will affect TTR and will be put in the context of this review. In the context of an ICU setting, the contribution of TTR is significant. Despite the complexity of the situation, TTR is not to be considered a test “for all seasons”. In the context of age, prolonged poor meal intake, chronic or acute illness, TTR needs to be viewed in a multivariable lens, along with estimated lean body mass, C-reactive protein, the absolute lymphocyte count, presence of neutrophilia, and perhaps procalcitonin if there is remaining uncertainty. Furthermore, the reduction of risk of associated complication requires a systematized approach to timely identification, communication, and implementation of a suitable treatment plan.
Keywords: cytokines